2012
DOI: 10.2136/vzj2012.0018
|View full text |Cite
|
Sign up to set email alerts
|

Root Water Uptake as Simulated by Three Soil Water Flow Models

Abstract: We compared four root water uptake (RWU) models of diff erent complexity that are all embedded in greater soil water fl ow models. The soil models used were SWAP (one-dimensional), FUSSIM2 (two-dimensional), and RSWMS (three-dimensional). Within SWAP, two RWU func ons were u lized (SWAP-macro and SWAP-micro). The complexity of the processes considered in RWU increases from SWAP-macro, to SWAP-micro, to FUSSIM2, to RSWMS. The objec ve of our study was to determine to what extent the RWU models diff ered when te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 28 publications
0
36
0
3
Order By: Relevance
“…Such an impact of the application of compensatory root-water uptake models has also been described in other studies and was claimed to be unrealistic and inconsistent with plant behaviour (e.g. Skaggs et al 2006, de Jong van Lier et al 2008, Shouse et al 2011, de Willigen et al 2012. However, in these studies, field verification of such compensatory root-water uptake models (e.g.…”
Section: Real Evapotranspiration (Etr)mentioning
confidence: 55%
See 3 more Smart Citations
“…Such an impact of the application of compensatory root-water uptake models has also been described in other studies and was claimed to be unrealistic and inconsistent with plant behaviour (e.g. Skaggs et al 2006, de Jong van Lier et al 2008, Shouse et al 2011, de Willigen et al 2012. However, in these studies, field verification of such compensatory root-water uptake models (e.g.…”
Section: Real Evapotranspiration (Etr)mentioning
confidence: 55%
“…However, in these studies, field verification of such compensatory root-water uptake models (e.g. ETr measurements by EC-systems with higher measurement frequency) was recommended, but not carried out (de Jong van Lier et al 2008, Shouse et al 2011, de Willigen et al 2012.…”
Section: Real Evapotranspiration (Etr)mentioning
confidence: 99%
See 2 more Smart Citations
“…Braud et al, 2005;Yadav et al, 2009;Dong et al, 2010). Comparisons with physically based models (Jarvis, 2011;de Willigen et al, 2012) that implicitly account for compensation showed that models not including compensation, like Feddes et al (1978), are less accurate with respect to crop transpiration and soil water content predictions under some circumstances, e.g. at a high root length density.…”
Section: Introductionmentioning
confidence: 99%